PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT DAN KETERAMPILAN BERWIRAUSAHA SISWA: - Syamiya, Estu; Sherylah , Ilah (Universitas Islam Syekh Yusuf, 2023)
This research aims to determine (1) the magnitude of the influence of entrepreneurship education on students' interest in entrepreneurship (2) the magnitude of the influence of entrepreneurship education on students' entrepreneurship skills. This research is causal associative research with a quantitative approach. The variables of this research are entrepreneurship education as the independent variable, entrepreneurial interest and skills as the dependent variable. This research is a population study with 126 student respondents. The data collection technique uses a questionnaire. The data analysis method used is simple linear regression.The results of this research show that (1) entrepreneurship education has a positive and significant effect on interest in entrepreneurship as indicated by the coefficient value (+0.550), with a significant value of 0.000 and a t-count value of 7.024. (2) Entrepreneurship education has a positive and significant effect on entrepreneurship skills as shown by the t value of 7.595 with a significance value of 0.000 and a coefficient value of (+0.707).